2022
DOI: 10.3390/plants11202683
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fertilization and Plant Density on the Dry Matter Yield and Quality of Black Mustard [Brassica nigra (L.) Koch]: An Alternative Forage Crop

Abstract: Black mustard [Brassica nigra (L.) Koch] is mainly cultivated as a seed crop, and there is a lack of information on biomass quality and its potential for animal feeding. A 2-year field experiment was set up in a split-plot design with 2 main plots (plant densities: 46 and 76 plants m−2), 4 sub-plots (fertilization levels: control, compost, urea with and without urease and nitrification inhibitors) and 3 replications for each treatment. The highest dry matter yield (17.55–18.34 tn ha−1) was observed in high-den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…On the contrary, in the seeds, Piętka et al [12] indicate a higher oil content in the seeds of the Warta cultivar (32.5%) compared to the Bamberka cultivar (31.4%), presenting two-year results from 12 field experiments: The third harvest, on average, 1.17 DM compared to the second harvest. This may explain the fact that Karydogianni et al [53], in experiments conducted with the use of black mustard biomass, obtained a higher crude fat content of 2.66 and 2.62% DM. The aim of these studies was to use the crop for fodder, so older plants were probably used in this experiment.…”
Section: Proximate Compositionmentioning
confidence: 94%
See 2 more Smart Citations
“…On the contrary, in the seeds, Piętka et al [12] indicate a higher oil content in the seeds of the Warta cultivar (32.5%) compared to the Bamberka cultivar (31.4%), presenting two-year results from 12 field experiments: The third harvest, on average, 1.17 DM compared to the second harvest. This may explain the fact that Karydogianni et al [53], in experiments conducted with the use of black mustard biomass, obtained a higher crude fat content of 2.66 and 2.62% DM. The aim of these studies was to use the crop for fodder, so older plants were probably used in this experiment.…”
Section: Proximate Compositionmentioning
confidence: 94%
“…20%. Karydogianni et al [53] found that the crude ash content in the aboveground biomass of black mustard was not dependent on plant density; however, plots with low density reached slightly higher values of this feature and it was 14.05% and 13.95% DM in the first and second experimental periods, respectively. Plots with a high density of plants were 13.89% and 13.63% DM for the same experimental periods.…”
Section: Proximate Compositionmentioning
confidence: 97%
See 1 more Smart Citation
“…Crop environment is referred to be comprised by agronomic practices such as seed rate, plant density, and fertilizer management, which had a significant effect on plant development, productivity, and quality (Dai et al, 2015;Karydogianni et al, 2022). High density is unfavourable because it promotes interplant competition for resources.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%